Pengembangan Manajemen Spiritual di Sekolah - Anam, Khoirul (Taallum: Jurnal Pendidikan Islam, 2016)
Sustainability of the school in the long term can be predicted from the values that espoused and used as share value. The process of selecting the virtue value that will be the foundationâs vision and mission for the school has been developing very dynamically with a model that is very varied. These models can be only as part of a school strategy or model that implements the noble values with pure consciousness. The values of spirituality seems increasingly been the trend as the noble values espoused school to ensure its long-term performance.